THE RELATIONSHIP BETWEEN MINDFULNESS AND FEAR OF FAILURE IN STUDENTS WHO ARE WORKING ON A THESIS AT PADANG STATE UNIVERSITY - wulandari, febri; Rinaldi (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Fear of failure is an emotional reaction that causes fear when in a situation that might cause failure. The phenomenon of fear of failure can be related to mindfulness, where mindfulness can reduce fear of failure. This study aims to determine the relationship between mindfulness and fear of failure in students who are working on a thesis at Padang State University. This study uses a correlational quantitative research design. The targets of this study were students who were working on a thesis at Padang State University using proportional sampling technique totalling 236 people. The mindfulness measuring instrument in this study used The Kentucky Inventory of Mindfulness Skills (KIMS) and the fear of failure scale using the Performance Failure Appraisal Inventory (PFAI). Based on the data analysis that has been done, the correlation value is obtained r = -0.298 and p = 0.000 (p < 0.05), which indicates that there is a significant negative relationship between mindfulness and fear of failure of students who are working on their thesis at Padang State University.